Structural and magnetic properties of electrospun FeCoNi magnetic nanofibers with nanogranular phases - Park, Ji Hea; Kweon, Soon C.; Kim, Sang Woo (SPRINGER, 2012)
Structural and magnetic properties of silicon/aluminum-added and -free FeCoNi magnetic alloy nanofibers with nanogranular phases prepared by electrospinning and subsequent annealing of the PVP-blended ternary metal precursors in hydrogen atmosphere were investigated. The FeCoNi magnetic alloy nanofibers with evenly distributed nanocrystalline phases were formed, which are identified as gamma-Fe1-xNix binary phase with face-centered cubic structure and alpha-CoFe phase with body-centered cubic structure. At elevated temperature, the alpha -> gamma structural martensitic transformation in the FeCoNi ternary alloys occurred due to the inhomogeneities in composition of the matrix during annealing of the alloy with metastable alpha-phase. In the Si/Al-added FeCoNi nanofibers, more than two phases with complicated-boundaries of the grains in and/or outside the nanofibers were formed as crystalline phases and amorphous phase. The amorphous phase consisted of Si and/or Al acted as an inhibitor diminishing alpha -> gamma transformation as well as an interparticle insulation layer. At low annealing temperature of 450 degrees C, the Si/Al-added nanofiber mainly consisted of metastable alpha-phase with a low-crystallinity surface structure and very small diameter of 13 nm was formed and showed an unexpectedly high coercivity, which attributed to the surface effects and/or high surface/volume ratio.
Keywords: FLUX DENSITY; NANOPARTICLES; SURFACE; FILM